Novos derivados sintéticos de alcaloides tetrahidroisoquinolínicos - Silva, Luiz André de Araújo (2016)
Alkaloids are secondary metabolites of great medical importance, covering a diverse group of nitrogen containing molecules in its structure, the number of alkaloid containing the tetrahidroisoquinolínico skeleton 1-substituted is extensive and impressive pharmacological versatility of this class arouses interest in experimental pharmacologists, the importance. This work has as objective, the synthesis of tetrahydroisoquinolines and provide material for future pharmacological studies both in-vivo and in-vitro. For the synthesis of phenyltetrahydroisoquinolinics alkaloids, benzyltetrahydroisoquinilinic and phenyltetrahydro-β-carboline the Pictet-Spengler reaction was aplicated. With the aim of expanding the pharmacological studies of the alkaloid (1-(3-dimethoxy-4-hydroxyphenyl)-7-methoxy-1,2,3,4,-tetrahydroisoquinoline (MTHP) your synthesis was repeated. 4 alkaloids were obtained, 2 phenyltetrahydroisoquinolinic (1-(3,5-dimethoxy-4-hydroxyphenyl)-7-methoxy-1,2,3,4-tetrahydroisoquinoline (73%) and 1-(2-hydroxyphenyl)-7-methoxy-1,2,3,4-tetrahydroisoquinoline (54%)), 1 phenyltetrahydro-β-carboline (1-(3,5-dimethoxy-4-hydroxyphenyl)-1,2,3,4,-tetrahydro-β-carboline (38%)) and 1 benzyltetrhydroisoquinilínic (1-(1-ethyl-3,4-metilenodioxidofenil)-6,7-dimethoxy-1,2,3,4-tetrahydroisoquinoline (87%)). From the material available for the pharmacological MTHP tests showed low toxicity without genotoxicity, its immunomodulatory mechanism in asthma is related to regulation of TH2 profile.